Biofortification of linseed as functional food for profitability and nutritional security: Biofortification of linseed as functional food for profitability and nutritional security - SUMA MOGALI,; LALITA JAGGAL,; O SRIDEVI, (Journal of Oilseeds Research, 2020)
Fish oil is the traditional source of dietary omega-3 fatty acids, while flaxseed oil can be used as a vegetariansource of dietary omega-3 fatty acids. The flaxseed hull is a concentrated source of lignan, which might possessimpressive cancer preventive properties, especially against breast and colon cancer. In functional foods arena, flaxseed has resurged as a potential ingredient with a vast array of medical benefits. Flaxseed supplemented food products are gaining popularity because of its high content of polyunsaturated fatty acids, protein, soluble fiber and phytochemicals. This paper describes about the development of biofortified linseed genotypes with enhanced alpha - linolenic acid (ALA), and lignan, predominantly the secoisolariciresinol diglucoside (SDG).